Cerclage Location and Gestational Age at Delivery - Estrada, Fatima; Karakash, Scarlett; SeeToe, Terry; Weedon, Jeremy; Minkoff, Howard (American Journal of Perinatology Reports, 2019)
Objective Multiple authors have suggested cerclage position is a determinant of “success.” We assessed the interaction between cervical length (CL), cerclage height (cerH), proximal residual length (PRL), gestational age at delivery, and rate of delivery ≤ 34 weeks, in this study.Study Design Present study is a retrospective cohort study of all cerclages placed at Maimonides Medical Center from 2006 to 2016. Outcomes: gestational age at delivery and delivery before 34 weeks; predictors: PRL, cerH, CL; and indications for cerclage: history (Hx), physical exam (PE), and ultrasound (US) indicated cerclage. A general linear model was used to predict power-transformed age at delivery from cerH, CL, and indication for cerclage. Subanalyses by indication were conducted. Logistic regression was used for delivery ≤ 34 weeks.Results The cerH by indication did not reach statistical significance (p = 0.090). When stratified by indications, the effect of cerH on age at delivery was apparent for Hx (adjusted R2 = 0.18, p < 0.001) and PE (adjusted R2 = 0.43, p = 0.004) cerclages but not for US cerclages (adjusted R2 = 0.08, p = 0.206). Logistic regression predicting delivery ≤ 34 weeks (n = 29) produced similar results.Conclusions For Hx and PE indicated cerclages, the location of the stitch may influence the timing of delivery. Specifically, the higher the cerclage, the more advanced the gestational age at delivery.
Keywords: preterm delivery; cervical cerclage; cervical length; cerclage height; proximal residual length; history indicated cerclage; physical exam indicated cerclage; ultrasound indicated cerclage